Women's Leadership in Islamic Perspective - Ilda Hayati (Institut Agama Islam Negeri (IAIN) Curup, 2016)
The existence of Prophet hadith which stated: “will not prosper. A people who submit their affairs to women”, has provoked serious debate among Muslims. It is concerning about the legality of a woman as public leaders. The resistance of groups who refused is directly proportional to the group that is not questioned about the gender as a leader. Different viewpoints among khilafiyah caused the difference. Besides reviewing the authenticity of hadith above, the following article explains the diversity of scholars’ opinions on women's leadership. Keywords: leadership, women, Islamic perspective